Hubungan Antara Karakteristik Individu, Pengetahuan Dan Sikap Operator Mesin Winding Unit Spinning Vi Dengan Kepatuhan Terhadap Instruksi Kerja Di Perusahaan Tekstil Semarang - Lidyawati, Herlinda; Kurniawan, Bina; -, ekawati (MEDIA KESEHATAN MASYARAKAT INDONESIA, 2010)
Compliance is following standard or law that is set up with clear, published by competent institutions in a particular field. Factors that affect compliance are demographic variables such as age, gender, ethnicity, social economic status and education, psychosocial variables such as intelligence, attitude towards health acceptance or repudiation of the rules, religious beliefs, or culture and cost. Working guideline instruction is a document contented of step by step detailed activity from one working unit or divisional function on work in technical term. The individual behavior is affected by predisposition, possibility and transducer factors. Predisposition fact is antecedent factor toward behavior and fundamental or motivation to performer. This observation is aimed to determine the relation between characteristics of individual, knowledge and working attitude with compliant tower working guideline instruction. The observation design which used in this observation is cross section whereby dependent variable is observed in same time. The population on this observation is entire winding machine operators unit spinning VI at textile manufacture of Semarang city. The sample in this observation is 44 respondents. The sample was drawn by accidental techniques. The data sources used in this observation consist of two types that were primary and secondary data. The data yielded is then analyzed by using SPSS 16 software version. The analysis conducted in this observation is using univariate and bivariate analyses by chi square testing. Based of the observation result it was determined there no meaning relationship between characteristics of individual, knowledge, and attitude with compliant towards working guideline instruction.